In Search of Skills to Overcome Life’s Obstacles in People Who Perform Supra-Personal Tasks - Zofia Remiszewska (Lubelski Rocznik Pedagogiczny, 2024)
Introduction: In their lives, people have to cope with various limitations or obstacles. How they cope with such problems may determine their future and, thus, optimise or destroy their existence.